Exploring Tri Hita Karana-Based CSR: A Sustainable Approach to Village Community Empowerment - Agra Gautama, Anak Agung Ngurah; Eddy Supriyadinata Gorda, Anak Agung Ngurah; Oka Suryadinata Gorda, Anak Agung Ngurah; Ngurah Restu Gautama, Anak Agung (Universitas Ibn Khladun Bogor, 2024)
This study explored the implementation of Corporate Social Responsibility (CSR) based on Tri Hita Karana in supporting community empowerment in Klungkung village, Bali. The method employed was a descriptive qualitative approach, utilizing data collection techniques such as interviews and documentation. The research informants included 10 purposively selected respondents, encompassing company representatives, village heads, and beneficiary communities to ensure relevant information. This study identified community participation and involvement in CSR programs focusing on education, health, and local economic improvement. Despite the positive impact, significant challenges remain, such as low community awareness and inadequate information about the CSR program of the company. By involving the community at every stage of planning and evaluation, the company can ensure the relevance and success of the program. The study emphasized the need for enhanced socialization, transparency, and two-way communication between the company and the community to overcome these obstacles. Involving local community leaders and youth in the socialization process is expected to improve community understanding and participation, fostering a more harmonious relationship. The results provided new insights into the dynamics between the company, village government, and community, highlighting the importance of collaboration in achieving sustainable community empowerment.